Chinese in french-speaking central Africa: understanding the trajectories of an ancient and multi-faceted presence - (:unkn) unknown (My University, 2022)
Since the beginning of the year 2000, the populations of French-speaking central Africa have discovered an increasingly growing Chinese community, very dynamic and practicing practically in all fields. If the presence of these Chinese communities is variously appreciated by the populations and their government, one wonders not only about the trajectories of their migration in Central Africa, but also, the historical motives which led them inside the French-speaking Central African countries. This work examines the historicity of the Chinese presence in Africa and the main question is to know how, and since when did the Chinese arrive in French-speaking Central Africa? To address this question, we mobilize a methodological approach which emphasizes the collection of written data. This study is part of a historical perspective and the theoretical framework is socio-history which examines, in the light of the historic past, the dynamics of Chinese migration in Central Africa. It emerges that the Chinese presence in this space is saving in East Africa and Southern and is above all based on solid historical considerations essentially motived by the needs for colonial labor. In this area, the current Republic of Congo has been an important point of support for the dissemination of the Chinese in other countries.
Keywords: African Research